2011
DOI: 10.1631/jzus.b1000179
|View full text |Cite
|
Sign up to set email alerts
|

Molecular authentication of geo-authentic Scrophularia ningpoensis

Abstract: Scrophularia ningpoensis has long been used in the Chinese Materia Medica for inflammation. Like other herbal medicines, S. ningpoensis collected from different localities may considerably differ in their therapeutic efficacy, and the one grown in Zhejiang Province is recognized as geo-authentic. However, it is difficult to confirm the geographical authenticity by similar morphological characteristics. In the present study, inter-simple sequence repeat (ISSR) markers were conducted to detect S. ningpoensis fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…These results revealed that this SCAR marker might be used in identification and authentication of C. wightii . Many reports are available in which SCAR markers have been used for authentication of medicinal plant species like Panax ginseng [ 65 ], bent-grass [ 66 ], Bamboo [ 67 ], Piper longum [ 68 ], Artemisia princeps and A. argyi [ 69 ], Phyllanthus emblica [ 70 ], strawberry [ 71 ] Jatropha curcas [ 72 , 73 ], Ganoderma lucidum [ 74 ], Pueraria tuberosa [ 75 ], Dendrobium candidum [ 76 ], Sinapis arvensis [ 77 ], Cornus officinalis [ 78 ], and Scrophularia ningpoensis [ 79 ]. Three SCAR markers of Phyllanthus species were developed from three specific RAPD sequences that can identify and differentiate the morphologically similar Phyllanthus species [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results revealed that this SCAR marker might be used in identification and authentication of C. wightii . Many reports are available in which SCAR markers have been used for authentication of medicinal plant species like Panax ginseng [ 65 ], bent-grass [ 66 ], Bamboo [ 67 ], Piper longum [ 68 ], Artemisia princeps and A. argyi [ 69 ], Phyllanthus emblica [ 70 ], strawberry [ 71 ] Jatropha curcas [ 72 , 73 ], Ganoderma lucidum [ 74 ], Pueraria tuberosa [ 75 ], Dendrobium candidum [ 76 ], Sinapis arvensis [ 77 ], Cornus officinalis [ 78 ], and Scrophularia ningpoensis [ 79 ]. Three SCAR markers of Phyllanthus species were developed from three specific RAPD sequences that can identify and differentiate the morphologically similar Phyllanthus species [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…(SNH, known as Xuanshen ) is a perennial herb native to Southeastern China. SNH cultivated in Zhejiang is a geo‐authentic crude drug among the most famous “Zhebawei” and “Panwuwei ” herbal medicines [6] . Scrophulariae Radix (SR), the dried root of SNH, has been used as a traditional Chinese medicine for centuries to treat various diseases including sore throat, abscesses, carbuncles and constipation [7] .…”
Section: Introductionmentioning
confidence: 99%
“…SNH cultivated in Zhejiang is a geo-authentic crude drug among the most famous "Zhebawei" and "Panwuwei" herbal medicines. [6] Scrophulariae Radix (SR), the dried root of SNH, has been used as a traditional Chinese medicine for centuries to treat various diseases including sore throat, abscesses, carbuncles and constipation. [7] SR is also used as the additive in health care products and functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the bioactive constituency, medicinal quality and efficacy of Chinese herbs are determined by their geo-authentic features (Chen et al 2011;Woo et al 1999;Liang et al 2013). Moreover, compared with other herbs, high-quality of herbs are better in clinical effects.…”
Section: Introductionmentioning
confidence: 99%